2013
DOI: 10.1124/dmd.113.052506
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytochrome P450 Enzymes by the E- and Z-Isomers of Norendoxifen

Abstract: Aromatase catalyzes the conversion of testosterone to estradiol and is the main source of endogenous estrogen in postmenopausal women. Aromatase inhibitors (AIs) are used to treat postmenopausal women with hormone receptor-positive breast cancer. Norendoxifen [4-(1-(4-(2-aminoethoxy)phenyl)-2-phenylbut-1-en-1-yl)phenol], an active metabolite of the selective estrogen receptor modulator tamoxifen, has been shown to be a potent competitive AI, with an IC 50 of 90 nM. To obtain data relevant to the clinical use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…In addition, Liu et al . also demonstrated the high selectivity of NorEND toward aromatase (CYP19) among other CYP450 enzymes, including CYP2B6, CYP2C9, CYP2C19, CYP2D6 and CYP3A , therefore suggesting that NorEND is a potent and selective aromatase inhibitor. NorEND has been previously shown to antagonize the activity of estrogen receptors in breast tissues, although its antagonism is reportedly weaker than those observed with (Z)‐4‐OHT and endoxifen .…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Liu et al . also demonstrated the high selectivity of NorEND toward aromatase (CYP19) among other CYP450 enzymes, including CYP2B6, CYP2C9, CYP2C19, CYP2D6 and CYP3A , therefore suggesting that NorEND is a potent and selective aromatase inhibitor. NorEND has been previously shown to antagonize the activity of estrogen receptors in breast tissues, although its antagonism is reportedly weaker than those observed with (Z)‐4‐OHT and endoxifen .…”
Section: Discussionmentioning
confidence: 94%
“…These results are generally consistent with those previously reported for structurally related compounds. 19, 20, 31, 32 …”
Section: Resultsmentioning
confidence: 99%
“…The bisphenol 9 was first prepared by McMurry cross-coupling of acetophenone ( 8 ) with 4,4'-dihydroxybenzophenone as described. 25 The bisphenol 9 was treated with an excess of MOMCl to afford the di-protected product 10 in good yield. The protected intermediate 10 underwent a series of reactions, including bromination with NBS, alkylation of potassium cyanide, and deprotection of the MOM groups with HCl to afford the nitrile 11 in very good yield.…”
Section: Resultsmentioning
confidence: 99%
“…24 Biological testing results confirmed the aromatase inhibitory activity of ( E,Z )-norendoxifen and further established high affinity for both ER-α and ER-β (Figure 2), establishing ( E,Z )-norendoxifen the first substance with potential dual AI and ER binding activity. 24, 25 The E - and Z -norendoxifen isomers ( E -5 and Z -5 ) were also prepared via stereoselective synthetic routes, and their biological activities revealed that E -norendoxifen is the more potent aromatase inhibitor, while Z -norendoxifen displayed greater affinity for both ER-α and ER-β. 24 To optimize efficacy and CYP selectivity, a series of norendoxifen analogues were subsequently designed and prepared using a structure-based drug design approach.…”
Section: Introductionmentioning
confidence: 99%